PengukuranTegangan Sisa Dengan metoda defleksi Dan Difraksi Sinar X - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
Deflection method is conducted splitting the specimen at its axis. Because of splitting, the plate is not static equilibrium. To reach the new static equilibrium state the plate will deflect. The mount of deflection is comparable with the residual stress exerted on its surface. X-Ray diffraction method uses the loan distance changes as a strain gauge. If the residual stresses on material exist, the atomic distance changes will be taken place and make a top angle fraction change.